INOVASI KERJA GURU BERSERTIFIKAT PENDIDIK DALAM PEMBELAJARAN DI SMA - Isman Stiawan; Rambat Nur Sasongko; Osa Juarsa (UNIVERSITAS BENGKULU, 2017)
The purpose of this study is to describe generally the innovation of teachers work certificate educators in senior high school 5 South Bengkulu. The method used in this study is a qualitative descriptive approach. Conclusions can be drawn from this research is the innovation of teachers working educators certificate in senior high school 5 South Bengkulu in performing learning tasks, planning a variety of learning methods and the use of multi media in learning. innovation of teachers working educators certificate in senior high school 5 South Bengkulu in coaching the students tried to prevent breaches of discipline than implementing punishment on students, innovation of teachers working educators certificate in senior high school 5 South Bengkulu in the running professions attempt to continue to pursue higher studies, seminars, workshops and training.